ANALISIS KESEHATAN DAN KESELAMATAN KERJA PADA INDUSTRI FURNITUR KAYU DENGAN METODE JOB SAFETY ANALYSIS - Devi, Anita Oktaviana Trisna; Setiyawan, Adi (JURNAL GAUNG INFORMATIKA, 2017)
Each production facility has a risk of danger for humans when it is used, it also happens in the production of wood furniture. Therefore, it is necessary to implement occupational health and safety management to reduce the risk of workplace accidents due to the use of production facilities. CV Rimba Sentosa, one of the woodfurniture companies has written accident data as many as 23 accidents in 2016. The figure increased 5-10% compared to the previous year's accident. Based on these facts,research was conducted to identify potential work accidents and control efforts, especially in the sawmill section. The method used in this study is Job Safety Analysis (JSA).The results of data processing show that the potential hazards that can arise due to the sawing process include low back pain, hand scratched saw blades, pollution from diesel engines, wood dust, and electric shock when turning on the engine. Hazard potential control efforts can be divided into two, namely engineering controls and  controls. The form of engineering controls that can be done is by giving  a wooden push and pulling limit on the bandsaw machine, serkel, and jointer so that thehand is not exposed to the saw blade. The administrative controls that can be done are by using PPE in the form of masks, glasses, shoes, and gloves.